Implementing Microsoft SharePoint 2019 : An Expert Guide to SharePoint Server for Architects, Administrators, and Developers. - Wanzer, Lewin (Packt Publishing, Limited, 2020)
SharePoint is one of Microsoft's most popular platforms and this book will cover the essentials such as governance, best practices, and configuration techniques that architects, developers, and administrators need to know to build robust infrastructure and server resources.
Description based upon print version of record.
Keywords: Microsoft SharePoint (Electronic resource); Intranets (Computer networks); Web servers.; Intranets.; Serveurs Web.; intranets.; Collaboration & group software.; Windows & variants.; Microsoft programming.; Computer networking & communications.; Computers -- Programming -- Microsoft Programming.; Computers -- Enterprise Applications -- Collaboration Software.; Computers -- System Administration -- Windows Administration.; Web servers